Eduquer et soigner : une éthique commune ? - Guillaume Durand (Recherches en Éducation)
Medical ethics and ethics of education both have to solve a fundamental problem: to reconcile respect for freedom and beneficent constraints. In the area of medical care, it is often for the benefit of the patient, a schizophrenic for instance, that we force him to take a treatment. In the area of education, any teacher would dream that his students always want and wish to learn, the reality of the teaching relationship is a constant back-and-forth movement between coercion and freedom, between the refusal and the desire to learn. In this paper, we are searching for, in Education and Medical Care, an ethics of autonomy which would be a middle way between paternalism and radical minimalism.